Review of the Role Calcium Silicate Ceramics for Bone Tissue Repair - Eka Putri, Suriati; Perdana, Rini (Hayyan Journal, 2024)
Bioinorganic science and the utilization of metal ions in the synthesis and design of new materials have received considerable attention in relation to their use as new biomaterials. One of the important roles of metal ions is to control the characteristics of the resulting biomaterials, namely their biological and chemical properties. To date, main group metal ions and transition metals have been used in the fabrication process of silicate and phosphate-based ceramics. Metal ions are used to modify their chemical composition and structure to overcome the shortcomings of silicate and phosphate-based ceramics. Calcium silicate (CaSiO3, CS) ceramics are biocompatible and bioactive. In this review, we consider the apatite-forming ability and biological properties of ion-doped CS ceramics such as bredigite, akermanite, monticellite, diopside, merwinite, hardystonite, baghdadite and sphene. Overall, according to the studies conducted on CS bioceramics, all of them may be good candidates for bone tissue regeneration